Treatment of Distal Upper Tract Urothelial Cancer with Distal Ureterectomy Preserves Renal Function without Increasing Local Recurrence Rate Compared with Radical Nephroureterectomy - Adhikari, Mahesh Bahadur; Tsang, Woon Chau; Tiong, Ho Yee (Nepalese Journal of Cancer, 2021)
Introduction: Kidney sparing surgery like endoscopic resection and distal ureterectomy has been recently proposed as alternative surgical options to manage distal Upper Tract Urothelial Cancer. This study aims to compare the surgical, oncological and functional outcomes of distal ureterectomy and Radical Nephroureterectomy for distal Upper Tract Urothelial Carcinoma. Methods and Material: Out of 57 patients with Upper Tract Urothelial Carcinoma treated surgically at a single institution between 2010 and 2016, nineteen patients had distal Upper Tract Urothelial Carcinoma. A retrospective review was performed on these 19 patients (11 Radical Nephroureterectomy and 8 distal ureterectomy). Radical Nephroureterectomy was performed using an open or laparoscopic approach (n= 4 and 7 respectively). All Distal Ureterectomy patients were performed via an open extra-peritoneal Gibson incision. Pelvic lymphadenectomy and Subsequent ureteroneocystostomy in the Distal Ureterectomy group was performed directly and was augmented by psoas hitch or using boari flap reconstruction. Demographic, clinical features and post-operative outcomes were compared between the Radical Nephroureterectomy and Distal Ureterectomy groups. Results: There was a trend towards shorter mean duration of surgery (238±34 vs. 286 ±90 min) and length of hospital stay (LOS) (7.6±2.8 vs. 17.3±20.7 days) in the Distal Ureterectomy group compared to the Radical Nephroureterectomy group (P=NS). Peri-operative Complication of Clavien grade 1-2 was seen in 4(33.33%) Radical Nephroureterectomy and 3 (37.5%) Distal Ureterectomy cases respectively. All patients had high grade Upper Tract Urothelial Carcinoma with equivalent pTNM staging in both groups with clear surgical margins. Immediate post-operative renal function improvement was statistically significant in the Distal Ureterectomy group (Radical Nephroureterectomy 2.27±5.93 vs 10.86±9.92 Distal Ureterectomy, p=0.034). Three out of 11 Radical Nephroureterectomy group patients required dialysis. Conclusions: Local recurrences were similar after Distal Ureterectomy and Radical Nephroureterectomy with equivalent pathological outcomes in distal Upper Tract Urothelial Carcinoma. There was a clear trend towards shorter hospital stay and better renal function preservation in favor of Distal Ureterectomy with fewer patients requiring dialysis.